GENETIC POLYMORPHISM OF 23 Y-CHROMOSOME SHORT TANDEM REPEAT LOCI IN THE KINH POPULATION OF VIETNAM - Hao, Ha Huu; Nhu, Nguyen Duc; Ha, Chu Hoang; Son, Le Van; Anh, Le Tuan; Lan, Dinh Thi; Thuy, Chu Thi; Thanh, Hoang Thai; Phuong Lien, Nguyen Thi (Vietnam Journal of Biotechnology, 2018)
Y-chromosome microsatellites or short tandem repeats (STRs) have been proved to be ideal markers to delineate the differences between individuals in human population. Nowadays, Y-STR testing using the PowerPlex® Y23 amplification kit is considered as an extremely sensitive analysis method and has the potential to be used to perform forensic caseworks, and to explore the complexity in population substructures. However, little is known about the forensic Y-chromosome databases in the Vietnam population. In this study, 23 Y-STR loci (DYS576, DYS389I, DYS389 II, DYS448, DYS19, DYS391, DYS481, DYS549, DYS533, DYS438, DYS437, DYS570, DYS635, DYS390, DYS439, DYS392, DYS393, DYS458 DYS456, DYS643, YGATAH4, and DYS385a/b) were investigated in 120 non-related males of the Kinh population in Northern Vietnam using PowerPlex® Y23 system kit (Promega). Our results showed that allele frequencies of 23 loci in the sample population, with the calculated average gene diversity (GD) for each locus, ranged from 0.24 (DYS438) to 0.92 (DYS385a/b). In addition, a total of 120 different haplotypes were found, all of them were unique. Therefore, we found that the haplotype diversity was 1 with a discrimination capacity of 100%, which serves as an essential prerequisite for using Y-chromosomal STR with PowerPlex® Y23 System kit in forensic application in Vietnam. We also compared genetic distances between Kinh population and 10 other neighboring populations from Y-chromosome haplotype reference database (YHRD). The Kinh population is significantly different from other populations. In conclusion, it was indicated that the 23 Y-STR loci were highly genetically polymorphic in the Kinh population in Vietnam and might be of great value in forensic application.